AN ANALYSIS ON THE DECISION MODEL OF SMART PLUS INSURANCE PRODUCT PURCHASE - Fitry Primadona; Ujang Sumarwan; Mukhamad Najib (Indonesian Journal of Business and Entrepreneurship (IJBE), 2016)
The purposes of this study were 1) to analyze the decision model of Smart Plus insurance product purchase and 2) to determine the criteria, sub-criteria, and alternative priorities in Smart Plus purchase decision model. The methods utilized in the study included a survey and interview (in-depth interview) by using an AHP analysis (Analytical Hierarchy Process) and processing software of "Expert Choice". The result of the first analysis indicated the four marketing mixes that had been performed (Price, Product, Process, and Place); while the second one showed that the purchase of Smart Plus product is based on the factors with the level of interest as follow: benefit (36.3%), premium (35.7%), membership process (14.6%), and provider (13.4%). The result of the second analysis revealed the important sub-criteria including premium offer, additional benefits, membership card, and temporary certificate from the medical specialist.Keywords: AHP, life insurance, marketing mix, purchase decision